Alternative methods of replacement of laboratory animals in biomedical research - KOSTOMITSOPOULOS (Ν.Γ. ΚΩΣΤΟΜΗΤΣΟΠΟΥΛΟΣ) N. G. (Journal of the Hellenic Veterinary Medical Society, 2018)
Society’s sensitivity on the use of laboratory animals, the need for the improvement of the scientific value of the results and the high costs urged the biomedical community to look for alternative methodologies which could replace or reduce the number of animals being used or refine the existing experimental techniques. Replacement alternatives can be classified, according to the applied methology, in in vitro and immunological techniques and in methods which use «lower» organisms or vertebrates at early developmental stages, mathematical or computer models, human studies or data banks. Using replacement alternatives may raise a lot of problems such as the quality of results. Validation of these methods is a complicated and time consuming process with high but fair hurdles which aim at human safety.